Control and Automation - Muresan, Cristina I.; Dulf, Eva H. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
A wide range of ongoing research in the areas of controller design and information engineering reveals that the pace of technological change in this domain seems to be accelerating. The primary focus is on futuristic segments ranging from robotics, genomics to chemical feedstock and electrical storage. The main objective of this special issue was to provide a forum for researchers and practitioners to exchange their latest theoretical and technological achievements and to identify critical issues and challenges for future investigation on topics regarding advanced automation and control techniques based on information system technologies.